Combination of photodynamic therapy with 5‐aminolaevulinic acid and microneedling in the treatment of alopecia areata resistant to conventional therapies: our experience with 41 patients. (12th September 2019) - Giorgio, C. M.; Babino, G.; Caccavale, S.; Russo, T.; De Rosa, A. B.; Alfano, R.; Fulgione, E.; Argenziano, G.
Summary: Alopecia areata (AA) is a complex immune‐mediated disorder, which is difficult to treat. The available treatment options seem to have limited benefit, help only some patients and have a high relapse rate. We evaluated a new therapeutic option for moderate to severe AA based on the combination of photodynamic therapy (PDT) with 5‐aminolaevulinic acid (ALA) and microneedling (MN). In total, 14 patients were enrolled, and these were randomly divided into 3 groups: Group A (MN alone; n = 9), Group B (ALA‐PDT alone; n = 15) and Group C (combination of MN and ALA‐PDT; n = 17). All patients were treated once every 3 weeks for a total of six treatments. The best clinical outcome was achieved in Group C, with complete hair regrowth observed in three patients, and an improvement of ≥ 50% and < 50% of the treated areas obtained in seven and six patients, respectively. Our report suggests that combination of ALA‐PDT with MN could be an additional therapeutic option in moderate to severe AA, as MN allows better skin penetration of ALA and subsequent indirect immunosuppression.